2017
DOI: 10.1080/1478422x.2016.1275418
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of stainless steel exposed to highly concentrated chloride solutions

Abstract: The characteristics of pitting corrosion of Type 304L stainless steel (SS) exposed to highly concentrated chloride solutions were studied through the evaluation of the corrosion potential, the pitting potential, the structure of the passive layer and the statistics of pitting depth and density. Both as-received and weld metal samples were studied. The weld metal sample was machined from the welding zone of a butt weld of Type 304L SS. The results showed an accelerated anodic dissolution and depressed film resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…The SS passivates in the atmosphere, but when in contact with the alkaline environment of the concrete, this passive layer is not stable and a new passivation process takes place [10][11][12]. Several studies with stainless steels reported their good corrosion resistance in chloride polluted environments, which vary in function of the SS chemical composition, the type of test performed (accelerated, natural), and the media (pore solution, mortar, or concrete) [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The SS passivates in the atmosphere, but when in contact with the alkaline environment of the concrete, this passive layer is not stable and a new passivation process takes place [10][11][12]. Several studies with stainless steels reported their good corrosion resistance in chloride polluted environments, which vary in function of the SS chemical composition, the type of test performed (accelerated, natural), and the media (pore solution, mortar, or concrete) [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[ 42 ] The passive layer thickness is inversely proportional to Q . [ 43 ] Thus, the base metal passive layer thickness was the highest, and it was adversely affected by both EB and GTA welding. A thicker passive film layer provides more effective protection against corrosion for similar chemical composition.…”
Section: Resultsmentioning
confidence: 99%